Regulation of Notch signaling by E3 ubiquitin ligases. (16th March 2021) - Dutta, Debdeep; Sharma, Vartika; Mutsuddi, Mousumi; Mukherjee, Ashim
Abstract : Notch signaling is an evolutionarily conserved pathway that is widely used for multiple cellular events during development. Activation of the Notch pathway occurs when the ligand from a neighboring cell binds to the Notch receptor and induces cleavage of the intracellular domain of Notch, which further translocates into the nucleus to activate its downstream genes. The involvement of the Notch pathway in diverse biological events is possible due to the complexity in its regulation. In order to maintain tight spatiotemporal regulation, the Notch receptor, as well as its ligand, undergoes a series of physical and biochemical modifications that, in turn, helps in proper maintenance and fine‐tuning of the signaling outcome. Ubiquitination is the post‐translational addition of a ubiquitin molecule to a substrate protein, and the process is regulated by E3 ubiquitin ligases. The present review describes the involvement of different E3 ubiquitin ligases that play an important role in the regulation and maintenance of proper Notch signaling and how perturbation in ubiquitination results in abnormal Notch signaling leading to a number of human diseases. Abstract : Notch signaling plays an important role during development by regulating multiple cellular events. This evolutionarily conserved pathway is tightly regulated by different E3 ubiquitin ligases. In this review, we provide an update regarding the E3 ligases and their role in regulation of Notch signaling. Additionally, we discuss several human diseases that are caused by these E3 ligases.